2007
DOI: 10.2118/96184-pa
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Alteration to Intermediate Gas-Wetting in Gas-Condensate Reservoirs at High Temperatures

Abstract: Wettability of two types of sandstone cores, Berea (permeability on the order of 600 md), and a reservoir rock (permeability on the order of 10 md), is altered from liquid-wetting to intermediate gas-wetting at a high temperature of 140°C. Previous work on wettability alteration to intermediate gas-wetting has been limited to 90°C. In this work, chemicals previously used at 90°C for wettability alteration are found to be ineffective at 140°C. New chemicals are used that alter wettability at high temperatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…The σ hw could also be affected. In our experience the use of fluorochemical polymers and its adsorption in rock substrate often increases the contact angle through water from 0° to about 150° by just reducing the surface energies of the substrate, and without affecting the surface tension in the gas‐liquid fluid systems 32. Figure 5 shows how capillary adhesion force is reduced as contact angle is increased between 0° and 60° with h = 3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The σ hw could also be affected. In our experience the use of fluorochemical polymers and its adsorption in rock substrate often increases the contact angle through water from 0° to about 150° by just reducing the surface energies of the substrate, and without affecting the surface tension in the gas‐liquid fluid systems 32. Figure 5 shows how capillary adhesion force is reduced as contact angle is increased between 0° and 60° with h = 3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of fluorosurfactants on wettability alteration at high temperatures has also been examined. Wettability results show that wettability alteration has a substantial effect on improving gas productivity at high reservoir temperatures [12,13]. Stanly and Firoozabadi [14] revealed that wettability of Berea and low permeability reservoir rocks can be permanently altered from liquid-wetting to intermediate gas-wetting.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of liquid hydrocarbon and water in the vicinity of wellbores was considered as the main restricting parameter making only 10% of original gas in place recoverable from this reservoir (Engineer 1985). A large number of theoretical and experimental studies have been devoted to understanding, modeling, and predicting the condensate accumulation and its associated impaired well productivity (O'Dell and Miller 1967;Fussell 1973;Danesh et al 1991;Henderson et al 1993Henderson et al , 1998Fevang and Whitson 1996;Mott 2002;Jamiolahmady et al 2003).…”
Section: Introductionmentioning
confidence: 99%